Kinetika Kimia Antibakteri Fraksi Alkana Alifatik Hasil Pirolisis Cangkang Biji Jambu Mete (CNS) - Musta, Rustam; Nurliana, Laily; Andraysno, Andraysno (Indonesian Journal of Chemical Research, 2020)
Chemical kinetics research antibacterial of aliphatic alkane fraction from the results of pyrolysis Cashew Nut Shell (CNS) (Annacardium occidentale L.) on Eschericia coli have been carried out. Cashew nuts are prepared by separating the shell and seeds for pyrolysis and purifying using a fractional distillation device. The results of E. coli anti-bacterial activity test from aliphatic alkane fractional distillation results of cashew nut shell pyrolysis products showed that the inhibitory power was different from each concentration variation of 100%, 75%, 50%, 25%, and 12.5%, with inhibitor zone: 8.02; 7.16; 5.56; 4.52 dan 4.26 mm which indicates that the inhibition is weak category for 12.5% and 25%, medium category for 50%, 75% and 100%. The clear zone that has been formed are calculated in terms of its chemical kinetics including the reaction order and the activity rate constant. The reaction order (n) antibacterial of aliphatic alkane fraction from the results of pyrolysis CNS on E. coli was 0.3145 with a constant activity rate of (k) = 1,7791.